The effect of dietary nitrate supplementation on physiology and performance in trained cyclists - McQuillan, J. A.; Dulson, D. K.; Laursen, P. B.; Kilding, A. E. (International Journal of Sports Physiology and Performance, 2017)
Purpose: To determine the effect of dietary nitrate (NO3 -) supplementation on physiology and performance in well-trained cyclists after 6-8 d of NO3 - supplementation.